IKOPZ: Measuring The Health Index of Zakat, Infaq, and Sadaqah Fund Management in BAZNAS Special Region of Jakarta Province - Amrullah, Muhamad Tohir; Nisa, Choirun; Pe, Cecilia Debora (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to measure the accountability of the management of Zakat, Infaq, and Sadaqah funds at the DKI Jakarta Provincial National Amil Zakat Agency or BAZNAS or BAZISS pecial Region of Jakarta. The use of the Zakat Management Organization Health Index or IKOPZ, developed by the BAZNAS Center for Strategic Studies(Puskas BAZNAS) through a mixed method approach with a sequential explanatory strategy was used in this study. The test was conducted by assessing financial and management factors with a total of eighty-fiveindicators. This research shows that BAZNAS of Special Region of Jakartafrom 2020 to 2021 consecutively has a goodhealth level condition because ofgood business management. The novelty in this research is the improvement of measurement based on IKOPZ which is more comprehensive than other methods such as Zakat Core Principle, National Zakat Index, and so on. As an example, IKOPZ measures financial factors consisting of activity, operations, liquidity, and growth, while management factors are measured through an assessment of general management, risk management, and sharia compliance. The research results have practical implications to support the accountability of ZIS fund management. For other zakat management organizations, this research can be a reference to develop and strengthen organizational governance. For some similar industries such as non-profit organizations, perhaps some indicators in financial and management factors in this study can also be used as a reference.